Synthesis and application of mixed spinel Mn0.4Cd0.6Cr2S2Se2: Structural, magnetic, and electrochemical sensing properties - Silvana Moris; Claudio Barrientos; Patricia Barahona; Catalina Cortes; Antonio Galdamez (Journal of the Chilean Chemical Society, 2024)
Herein we report the solid synthesis, structural characterization, magnetic behavior, and electrochemical sensing properties of Mn0.4Cd0.6Cr2S2Se2. Single‐crystal X‐ray diffraction analysis showed that Mn0.4Cd0.6Cr2S2Se2 crystallizes in a spinel‐type structure. Powder X-ray diffraction patterns and Rietveld refinement data revealed that this selenide phase is consisted of cubic Fdm space group. Magnetic field cooling (MFC) measurements indicated an enhancement in ferromagnetic interactions relative to the ferrimagnetic compound Mn0.4Cd0.6Cr₂S₄, which can be attributed to the substitution of sulphur by selenium. The electrochemical response of modified glassy carbon electrodes with Mn0.4Cd0.6Cr2S2Se2 was increased, the peak current is increased 4-fold, from 20.15 µA to 83.52 for GC, and GC-Mn0.4Cd0.6Cr2S2Se2 respectively by differential pulse voltammetry, and thus it could be used to design an electrochemical sensor to quantify nitrocompounds, considered pollutants and toxic agents for humans, plants, and animals.